Peningkatan Kompetensi Pembelajaran Pendidikan Seks pada Anak Usia Dini pada Guru TK ABA se-Kota Medan - Qaulan Raniyah; Rahimah Rahimah; Evicenna Yuris (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
Early childhood sex education is still a sensitive issue and is often avoided in educational practices in PAUD institutions, even though instilling the right understanding from an early age is very important to form children's awareness of their bodies, personal boundaries, and self-protection. This Community Partnership Program aims to improve the competence of PAUD teachers in understanding, designing, and delivering sex education that is appropriate to the stages of child development. Activities are carried out through training, workshops, and mentoring involving 110 teachers from 40 ABA se Kota Medan. The material presented includes basic concepts of children's sex education, communication strategies, and the role of teachers in preventing sexual violence. The evaluation results showed a significant increase in teacher understanding, as indicated by an increase in scores from pre-test to post-test. In addition, teachers also showed changes in attitude and readiness to integrate this material into daily learning activities. This program proves that partnership-based interventions between universities and the community are able to answer real needs in the field and support preventive child protection efforts from an early age.